The Year in Hungarian Cardiology 2022: Heart failure and cardiomyopathies - Habon, Tamás; Rábai, Miklós; Halmosi, Róbert (Cardiologia Hungarica (Budapest), 2023)
In the year 2022 a large number of remarkable scientific papers were published in the field of heart failure and heart muscle disease, to which the Hungarian Heart Failure community contributed with influential scientific activity. Results of landmark randomized clinical trials were published, and in recognition of the clinical and scientific activity of the Hungarian centers, notable activity was also demonstrated publishing these studies. In the field of cardiomyopathies several novel results were published in 2022. In connection with hypertrophic cardiomyopathy (HCM) a landmark paper described the genetic architecture of the affected Hungarian population. An editorial comment was published in a highly ranked journal describing the myosin motor inhibition concept. An interesting paper about a retrospective analysis of cardiac amyloidosis patients, and MR specific differences between left ventricular noncompaction and dilated cardiomyopathy was published. Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) was an ongoing pandemic in 2022 resulting in millions of deaths worldwide, affecting the heart of as much as 20–25% of those infected and causing several cardiac complications. Studies were published about the screening for myocardial injury and about the immunological response on disease itself and the vaccination against the virus. A joint scientific statement by the ESC also dealt with this topic. An impressive study was published about the prognostic value of anemia in patients with preserved, and mildly reduced and recovered ejection fraction and about the feasibility of baroreflex sensitivity measurements in heart failure subjects. In relation to drug therapy, a study is also worth mentioning about the cardiac efficacy and overall safety of SGLT2 inhibitors in patients treated with anthracyclines, and a network meta-analysis of randomized trials, analyzing the cardiovascular outcomes in patients treated with gliflozins. Finally, a focused issue of Cardiologia Hungarica on heart failure and myocardial diseases should be highlighted.